2018
DOI: 10.1016/j.pedn.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on Nurse-led Consultations Within a Pilot Structured Transition Program for Young Adults Moving From an Academic Tertiary Setting to Community-based Type 1 Diabetes Care

Abstract: Patient autonomy and privacy should be respected during this developmental period. Nurses taking a humanistic approach towards accompanying and supporting the patient can enhance the therapeutic relationship during transition and promote continuity of care. Transition nurses can use technical competence and therapeutic education to empower patients for self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…[37] Research has shown that the NPR has a profound impact on patient satisfaction, especially in HD settings, where treatment involves prolonged (about four hours per session) and repeated (three times a week) interaction between patients and nurses. [8,16,[38][39][40][41] Our data have shown that, overall, patients perceived medium to high levels of caring, with seven out of ten dimensions rated three or higher on a scale of 1 to 5. These ratings are in line with previous observations in similar contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Research has shown that the NPR has a profound impact on patient satisfaction, especially in HD settings, where treatment involves prolonged (about four hours per session) and repeated (three times a week) interaction between patients and nurses. [8,16,[38][39][40][41] Our data have shown that, overall, patients perceived medium to high levels of caring, with seven out of ten dimensions rated three or higher on a scale of 1 to 5. These ratings are in line with previous observations in similar contexts.…”
Section: Discussionmentioning
confidence: 99%
“…These ratings are in line with previous observations in similar contexts. [8,41] According to Watson, [20,21] the ten caring factors describe an NPR where nurses can show compassion, respect, kindness, and impartiality, regardless of the patient's culture, beliefs, or orientations. Consequently, the higher the rating, the more patients perceive that nurses see them as people and not merely carriers of disease, support their efforts, adopt a teaching style focused on problem-solving, and are respectful of their intimacy and needs.…”
Section: Discussionmentioning
confidence: 99%
“…Some tools measure actual, that is, observable, behaviour (e.g., Caring Behaviours Inventory, Wolf, Giardino, Osborne, & Ambrose, ), whereas others focus on hypothetical behaviour, such as perceptions regarding the importance of certain behaviours or nurses’ self‐reported competence to perform those behaviours (e.g., CARE‐Q, Larson, ). Many tools incorporate items focused on aspects of the relationship in addition to behaviour, such as nurses’ attitudes (e.g., Caring Nurse–Patient Interaction Scale, Zoni et al, ). Some tools focus only on nursing whilst others combine a measure of the nurse–patient relationship with measures of other aspects of health care, such as physician–patient relationships (e.g., Consumer Assessment of Healthcare Providers and Systems, Goldstein, Farquhar, Crofton, Darby, & Garfinkel, ).…”
Section: Introductionmentioning
confidence: 99%
“…This literature review identified gaps and strengths in the care of pediatric patients transitioning to adult care. Zoni et al (2018) identified more research is needed to identify best practices for transitional care programs, but nurse-led programs are a valid tool to support transition. Garvey et al (2017) recognized there is a need for development and evaluation of standardized transitional education tools and that pediatric endocrinology visits focused on transitional issues may decrease gaps in care at transition to adult care.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Agarwal et al (2017) and Pierce et al (2017) both used the SMART model as their conceptual framework. Zoni et al (2018) and Garvey et al (2017) both 12 used SCI to assess their sample. Pierce et al (2017) and Kiziler et al (2018) found that self-care is a vital outcome of transition clinics.…”
Section: Gaps In the Literaturementioning
confidence: 99%